Stress Management by the Agricultural Officers - T. Lakshmi (Journal of Agricultural Extension Management, 2025)
Stress is the spice of life and we would have to live with stress from womb to tomb. Stress is common in the world of day today activities and at minimal level it may not be hazardous to individuals. But when individuals experience extreme stress it affects all aspects of human behaviour including the work in which he is actively involved. Stress reduces the efficiency in working people and at times becomes so overbearing that normal coping mechanisms of working people fail and they start seeking refuge in drugs, alcohol or may developmental illness. So an optimum level of stress is necessary to live happily. The optimum stress level varies and is defined as the stress level at which an individual can function efficiently without feeling any physical or mental ill effect. At optimum stress level you feel fit and fine